No Justice, Only Struggle: Academic Restructuring and Library Labour in Authoritarian Capitalism - Zvyagintseva, Lydia; Ribaric, Tim (Canadian Journal of Academic Librarianship / Revue canadienne de bibliothéconomie universitaire)

(untitled) (Canadian Association of Professional Academic Librarians / Association Canadienne des Bibliothécaires en Enseignement Supérieur, 2022)
2022 has been a year of overlapping crises. The so-called “Freedom Convoys” paralyzing Canadian communities, the COVID-19 pandemic continuing to cause excess death and disability, the war in Ukraine, the intensifying effects of climate change, and increasing inflation have all signaled that we find ourselves in a new era, one that can be described as authoritarian capitalism. In this article, we view the restructuring of Canadian universities as yet another facet of authoritarian capitalism, which uses overlapping crises to further proletarianize library labour and fully subsume it into the “learning factory.” Using Sandro Mezzadra and Brett Neilson’s theorization of the politics of capital’s operations, we examine the library restructuring processes taking place at four Canadian universities: Alberta, Brock, Laurentian, and OCAD. We view the reorganizations taking place there as efforts on behalf of university administrators to use the intensification of global forces of capitalism to exploit academic librarian labour. Ultimately, we argue that Canadian librarians are witnessing both formal and real subsumption in Canadian universities, precipitated by the overlapping crises outlined earlier. As a result, we insist that librarians need to develop a politics of struggle to build collective consciousness and action in the face of authoritarian capitalism.